The Implementation of Market Models Using VBA - Goossens, Francois (The Wiley Finance Series, 2015)
Cover -- Title Page -- Copyright -- Contents -- Preface -- Acknowledgements -- Abbreviations -- About the Author -- Chapter 1 The Basics of VBA Programming -- 1.1 Getting started -- 1.2 VBA objects and syntax -- 1.2.1 The object-oriented basic syntax -- 1.2.2 Using objects -- 1.3 Variables -- 1.3.1 Variable declaration -- 1.3.2 Some usual objects -- 1.3.3 Arrays -- 1.4 Arithmetic -- 1.5 Subroutines and functions -- 1.5.1 Subroutines -- 1.5.2 Functions -- 1.5.3 Operations on one-dimensional arrays -- 1.5.4 Operations on two-dimensional arrays (matrices) -- 1.5.5 Operations with dates -- 1.6 Custom objects -- 1.6.1 Types -- 1.6.2 Classes -- 1.7 Debugging -- 1.7.1 Error handling -- 1.7.2 Tracking the code execution -- Chapter 2 Mathematical Algorithms -- 2.1 Introduction -- 2.2 Sorting lists -- 2.2.1 Shell sort -- 2.2.2 Quick sort -- 2.3 Implicit equations -- 2.4 Search for extrema -- 2.4.1 The Nelder-Mead algorithm -- 2.4.2 The simulated annealing -- 2.5 Linear algebra -- 2.5.1 Matrix inversion -- 2.5.2 Cholesky decomposition -- 2.5.3 Interpolation -- 2.5.4 Integration -- 2.5.5 Principal Component Analysis -- Chapter 3 Vanilla Instruments -- 3.1 Definitions -- 3.2 Fixed income -- 3.2.1 Bond market -- 3.2.2 Interbank market -- 3.3 Vanilla derivatives -- 3.3.1 Forward contracts -- 3.3.2 Swaps -- 3.3.3 Bond futures -- 3.4 Options basics -- 3.4.1 Brownian motion -- 3.4.2 Ito integral -- 3.4.3 Ito formula -- 3.4.4 Black-Scholes basic model -- 3.4.5 Risk-neutral probability -- 3.4.6 Change of probability -- 3.4.7 Martingale and numeraires -- 3.4.8 European-style options pricing -- 3.5 First generation exotic options -- 3.5.1 Barrier options -- 3.5.2 Quanto options -- Chapter 4 Numerical Solutions -- 4.1 Finite differences -- 4.1.1 Generic equation -- 4.1.2 Implementation -- 4.2 Trees -- 4.2.1 Binomial trees -- 4.2.2 Trinomial trees.